Community partnership for healthy sleep: Research protocol. Issue 1 (26th December 2017) - Redeker, Nancy S.; Ordway, Monica R.; Banasiak, Nancy; Caldwell, Barbara; Canapari, Craig; Crowley, Angela; Fenick, Ada; Jeon, Sangchoon; O'Connell, Meghan; Sude, Leslie; Sadler, Lois S.
ABSTRACT: Beginning early in life, sleep health, including adequate quality, quantity, and consistent sleep routines, is critical to growth and development, behavior, and mental and physical health. Children who live in economically stressed urban environments are at particular risk for sleep deficiency and its negative consequences. Although efficacious sleep health interventions are available, few address the context of economically stressed urban environments. The purpose of this paper is to describe a two‐phase protocol for an ongoing NIH/NINR‐funded community‐engaged study designed to understand the perspectives of parents, community child care and pediatric health care providers about sleep habits, factors that contribute to sleep and sleep habits, sleep difficulty, and potentially useful sleep promotion strategies among children living in economically stressed urban environments. The social‐ecological model guides this study. Phase I employs a convergent mixed‐methods design, in which we are conducting semi‐structured interviews with parents, childcare providers, and primary health care providers. We are collecting 9 days of objective sleep data (wrist actigraphy) from children who are 6–18 months ( n  = 15) and 19–36 months of age ( n  = 15) and parent reports of sleep and sleep‐related factors using standard questionnaires. In Phase I, we will use a qualitative descriptive approach to analyze the interview data, and descriptive statistics to analyze the survey and actigraph data. In Phase II, we will use the information to develop a contextually relevant program to promote sleep health. Our long‐term goal is to improve sleep health and sleep‐related outcomes in these children.